INOVASI KURIKULUM PEMBELAJARAN IPAS BERBASIS PROYEK TERINTEGRASI CULTURALLY RESPONSIVE TEACHING UNTUK SISWA SEKOLAH DASAR - Siti Raihan; Amir Pada; Andi Makassau; Nur Abidah Idrus; Andi Dewi Riang Tati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
IPAS (Science and Social Studies) learning in elementary schools still faces challenges, including low student engagement and a lack of integration of local cultural values in learning. This study aims to develop a project-based IPAS learning device integrated with Culturally Responsive Teaching (CRT) for fifth-grade elementary school students in Makassar City. The study employed the 4D development model (Define, Design, Develop, Disseminate), which includes needs analysis, instructional design, product development, and limited trials. The trial was conducted in two elementary schools, involving two teachers and 62 students. Data were collected through learning activity observations, expert validation (material and media), student and teacher questionnaires, and learning outcome tests. Validation by two material experts and two media experts showed the product to be in the